Campus da Universidade Federal de Santa Maria: inventário do patrimônio moderno (1960-1970) - Wolle, Alberto Brilhante (2019)
The present essay is based on the preservation of the modern architectural patrimony on the campus of University Federal de Santa Maria, RS, a significant sample of this unique period of Brazilian architecture, encompassing the period between the 1960s and 1970s.This work was motived by big changes that misleaded texts and the original perception of its original urban design and the building’s own characteristic. To help keeping data and preservation of this architectural typology, it was used the instrument on the list of the Integrate System of Knowledge and Mangement (SICG), developed by The Historical and Artistic Heritage National Institute (IPHAN). For the accomplishment of this work, the methodology used started with the bibliographic review about the referential theories of subjects as culture, values assignment and patrimony, concepts of Inventory, University as well as constitution and consolidation of Modern architectural movement, from international to local scale, beyond the process of implementation and characterization of the UFSM campus. Based on these data, the target constructions were identified, selected and registered in inventory files supported by surveys and documental researches in the Division of General Files and in the Register Center of UFSM. The results confirm the understanding of the subject of study as part of the modern movement that was being consolidated as a precedent which was expanding throughout Brazil. On the other hand, the large period to build the constructions, most of the times without manual, neither conservation nor preservation projects. Besides that, the changes and new insertions in those buildings which reflect the suppression of elements and the loss of important architectural characteristics, proclaimed by the ideas of modernism in right at that time. As a result, the inventory was made and exposed as an appendix in the end of the essay, in order to deepen new studies and promote actions that aim to preserve that kind of architectural typology, whose UFSM campus is an important sample to be considered, valued and preserved.